Formulasi dan Karakterisasi Sifat Fisikokimia serta Organoleptik Cookies Berbahan Tepung Gembili dan Mocaf dengan Penambahan Bubuk Kayu Manis - Arvi Yashinta Andeswari; Maria Ulfah; Mohammad Prasanto Bimantio (BIOFOODTECH : Journal of Bioenergy and Food Technology, 2026)
This study aims to examine the effect of varying ratios of gembili tuber flour and mocaf flour, as well as cinnamon powder concentration, on the chemical and organoleptic characteristics of cookies. The study used a two-factor Complete Block Design (CBD), namely the gembili flour to mocaf flour ratio (80 g:20 g, 60 g:40 g, 50 g:50 g) and cinnamon powder concentration (0.5%, 1%, 1.5%) with two replicates. The parameters analyzed included moisture content, ash, protein, fat, crude fiber, carbohydrates, and organoleptic tests (color, aroma, taste, and texture). The results showed that the flour ratio had a significant effect on all parameters except color, taste, and texture. Meanwhile, the addition of cinnamon powder had a significant effect on moisture content, ash, fiber, fat, carbohydrates, and color, but had no effect on protein or the organoleptic tests for aroma, taste, and texture. The best cookies were produced in treatment T2B3 (60% gembili flour : 40% mocaf with 1.5% cinnamon), yielding a moisture content of 2.69%, ash 5.21%, crude fiber 5.86%, fat 12.54%, protein 4.16%, carbohydrates 76.73%, and a panelist preference score of 5.45 (in the “agak suka” category).